LIDAR-based turbulence intensity calculation using glide-path scans of the Doppler LIght Detection And Ranging (LIDAR) systems at the Hong Kong International Airport and comparison with flight data and a turbulence alerting system - Pak Wai Chan (Meteorologische Zeitschrift, 2010)
Glide-path scans of the LIght Detection And Ranging (LIDAR) systems have been devised by the Hong Kong Observatory (HKO) for windshear alerting over the Hong Kong International Airport (HKIA). This paper studies the use of glide-path scans in the alerting of low-level turbulence which may be encountered by the aircraft. Turbulence intensity, namely, eddy dissipation rate (EDR), is calculated by structure function approach based on the radial velocity data obtained in the glide-path scans. Two methods have been employed in the calculation, namely, the azimuthal structure function and the longitudinal structure function. They are found to give generally consistent EDR values. The LIDAR-based EDR estimates are then compared with the EDR values derived from flight data. Results show that the two sets of EDR data are comparable with each other. Application of LIDAR-based EDR in turbulence alerting is demonstrated in two typical examples of low-level turbulence at HKIA. Such EDR values are found to be consistent with pilots' subjective perception of the turbulence. Finally, EDR values provided by the operational Windshear and Turbulence Warning System (WTWS) of HKO are compared with those obtained by the LIDAR, demonstrating the operational benefits of including the LIDAR-based EDR in the alerting of mechanical turbulence.